Nonsurgical Approaches for Managing Hypersplenism in Thalassemia - Abdullah Talal Almohammadi (Journal of Applied Hematology)
Hypersplenism is a common manifestation of transfusion-dependent thalassemia. It results from extramedullary hematopoiesis and ineffective erythropoiesis. The end result of massive splenomegaly and chronic pancytopenia requiring transfusion debilitates the patient and implies a huge burden on the medical system. Classically, splenectomy has been the favorable approach, but the newer pharmacological approaches reversing the pathology or the minimally invasive radiological procedure can push splenectomy as the last resort and ultimately save the patients from the morbidity associated with splenectomy.